Representations about discrimination practices in the education system built by Gypsies (Ciganos) in the Lisbon Metropolitan Area (Portugal) - Mendes, M. M. (2017)
In Portugal, Gypsies (Ciganos) are categorized as ethnical and minority group, and they are particularly vulnerable to poverty and social exclusion. There is no doubt that they are one of the groups that rise more antipathy among the other Portuguese. In what concerns the "social images" built by the dominant society, there is a negative evaluation of the Gypsies and this image has persisted and resisted so far. Therefore, Gypsy identity and culture are considered marginal. However, the historical discrimination against Gypsies and the existence of a scarce interaction with the non-Gypsy society are some interesting results coming out from a qualitative study finished in 2006 about social representations and emotions that emerged in discriminatory contexts related with the educational system. One of the main objectives of this article is to find how Gypsies represent the school, the formal education, and the social agents that intervene in this educational context, like teachers, other school workers, and other students (non-Gypsies). It is possible to notice some discourses that revealed negative perceptions and rejection feelings incorporated by some Gypsies. They feel that they are treated like "inferior" persons and not recognized by the whole society.